Soluble amyloid-β precursor peptide does not regulate GABAB receptor activity - Pascal Dominic Rem; Vita Sereikaite; Diego Fernández-Fernández; Sebastian Reinartz; Daniel Ulrich; Thorsten Fritzius; Luca Trovo; Salomé Roux; Ziyang Chen; Philippe Rondard; Jean-Philippe Pin; Jochen Schwenk; et al. (eLife, 2023)
Amyloid-β precursor protein (APP) regulates neuronal activity through the release of secreted APP (sAPP) acting at cell surface receptors. APP and sAPP were reported to bind to the extracellular sushi domain 1 (SD1) of GABAB receptors (GBRs). A 17 amino acid peptide (APP17) derived from APP was sufficient for SD1 binding and shown to mimic the inhibitory effect of sAPP on neurotransmitter release and neuronal activity. The functional effects of APP17 and sAPP were similar to those of the GBR agonist baclofen and blocked by a GBR antagonist. These experiments led to the proposal that sAPP activates GBRs to exert its neuronal effects. However, whether APP17 and sAPP influence classical GBR signaling pathways in heterologous cells was not analyzed. Here, we confirm that APP17 binds to GBRs with nanomolar affinity. However, biochemical and electrophysiological experiments indicate that APP17 does not influence GBR activity in heterologous cells. Moreover, APP17 did not regulate synaptic GBR localization, GBR-activated K+ currents, neurotransmitter release, or neuronal activity in vitro or in vivo. Our results show that APP17 is not a functional GBR ligand and indicate that sAPP exerts its neuronal effects through receptors other than GBRs.